Kadar Hemoglobin pada Sampel Darah Petugas Stasiun Pengisian Bahan Bakar Umum (SPBU) - Rosalinda Zakhwa (Jaringan Laboratorium Medis, 2021)
Hemoglobin is a part of erythrocytes that serves to transport oxygen and carbon dioxide in tissues. Hemoglobin levels in the blood may decrease one of which is influenced by exposure to lead from the environment. Places that are at high risk for exposure to air lead one of them is at gas stations (Public Refueling Stations). The purpose of this study is to determine hemoglobin levels in kedungrandu gas station officers, Kec. Patikraja, Banyumas. This type of research is a non-experimental observational study. The method of measuring hemoglobin levels using strip test in the form of POCT (Point Care of Testing) tool. This method uses capillary blood samples from 20 respondents with criteria of male sex and aged 21-60 years. The result of this study was as many as 6 people (30%) of the total respondents had low hemoglobin levels, while 14 people (70%) have normal hemoglobin levels. The average hemoglobin level in the blood sample of kedungrandu gas station officers, Kec. Patikraja, Banyumas is 14.41 mg/dl or normal.